Information and informatics literacies of first-year medical students. - Richardson, Joshua E.; Bouquin, Daina R.; Tmanova, Lyubov L.; Wright, Drew (Journal of the Medical Library Association, 2015)
Purpose: The study evaluated medical students' familiarity with information literacy and informatics during the health sciences library orientation. Methods: A survey was fielded at the start of the 2013 school year. Results: Seventy-two of 77 students (94%) completed the survey. Over one-half (57%) expected to use library research materials and services. About half (43%) expected to use library physical space. Students preferred accessing biomedical research on laptops and learning via online-asynchronous modes. Conclusions: The library identified areas for service development and outreach to medical students and academic departments.